2001
DOI: 10.1128/jvi.75.17.8054-8062.2001
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation of Citrus Tristeza Virus Isolates from California and Spain: Evidence for Mixed Infections and Recombination

Abstract: We examined the population structure and genetic variation of four genomic regions within and between 30 Citrus tristeza virus (CTV) isolates from Spain and California. Our analyses showed that most isolates contained a population of sequence variants, with one being predominant. Four isolates showed two major sequence variants in some genomic regions. The two major variants of three of these isolates showed very low nucleotide identity to each other but were very similar to those of other isolates, suggesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
157
1
12

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 213 publications
(187 citation statements)
references
References 49 publications
17
157
1
12
Order By: Relevance
“…No relationship was found among isolates according to collection time or spatial separation. These results agree with those of other authors who have reported a high spatial and temporal genetic stability for several RNA viruses, suggesting that selective pressures to preserve biological functions are stronger than speciation due to geographic separation [14,23,32,34,40].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…No relationship was found among isolates according to collection time or spatial separation. These results agree with those of other authors who have reported a high spatial and temporal genetic stability for several RNA viruses, suggesting that selective pressures to preserve biological functions are stronger than speciation due to geographic separation [14,23,32,34,40].…”
Section: Discussionsupporting
confidence: 83%
“…However, selective pressures imposed by certain aspects of viral biology (e.g., host type and range) may limit genetic diversity [31,33,34,40,41].…”
Section: Introductionmentioning
confidence: 99%
“…The Rubio et al (2001) primers was used which was designed based on the T30 genotype, but has been shown to also amplify strains from the VT, T3, B165, HA16-5 and RB genotypes (Read and Pietersen, 2015). Amplicons were purified using the Promega Wizard ® SV Gel and PCR Cleanup System (Promega, Madison, WI) according to the manufacturer"s instructions and ligated into the p-GEM ® -T Easy vector.…”
Section: Cloning and Sequencing Of The Orf 1a Fragmentmentioning
confidence: 99%
“…The acknowledged genotypes of CTV are continually being expanded, and thus far include T36, T30, T3, VT, B165, HA16-5, T68 and RB (Albiach-Marti et al, 2000;Harper, Dawson, and Pearson, 2010;Harper, 2013;Karasev et al, 1995;Mawassi et al, 1996;Melzer et al, 2010;. The CTV population of a single host may contain many different genotypes as the longevity of citrus plants allows for repeated infections of various CTV sources through aphid transmission (Rubio et al, 2001). CTV can be controlled through mild strain cross-protection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation